2015
DOI: 10.1055/s-0034-1380454
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Three-Component Route for the Synthesis of Rhodanine Derivatives in Water

Abstract: A one-pot three-component route for the synthesis of rhodanine derivatives by the reaction of primary amines, carbon disulfide, and maleic anhydride in water is described. The reactions proceed via a sequential Michael addition-intramolecular amide bond formation. Bis(rhodanine) derivatives were also synthesized by using a diamine in this protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…As a part of our continued interest in the development of practical, safe, and environmentally friendly procedures for some important organic transformations and synthesis of chromenes , a convenient and facile one‐pot three‐component method for the synthesis of 4 H ‐chromenes in the presence of ZrOCl 2 ·8H 2 O as catalyst in water under thermal condition has been described (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…As a part of our continued interest in the development of practical, safe, and environmentally friendly procedures for some important organic transformations and synthesis of chromenes , a convenient and facile one‐pot three‐component method for the synthesis of 4 H ‐chromenes in the presence of ZrOCl 2 ·8H 2 O as catalyst in water under thermal condition has been described (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Nasiri et al reported a one‐pot route for the synthesis of 2‐thioxo‐1,3‐thiazinane‐4‐one derivatives from the reaction of primary amines and carbon disulfide in the presence of acryloyl chloride under solvent‐free conditions . Recently we reported a one‐pot three‐component route for the synthesis of rhodanine derivatives via the reaction of primary amines, carbon disulfide, and maleic anhydride in water . As a part of our recent studies on the expanding of green methods to the synthesis of dithiocarbamates, herein we investigated the one‐pot three‐component reactions of primary and secondary amines, carbon disulfide, and itaconic anhydride in water, as a green route for the synthesis of 2‐(3‐alkyl‐4‐oxo‐2‐thioxo‐1,3‐thiazinan‐5‐yl)acetic acid, a precursor of sulfur analogues of uracil, and succinic acid derivatives containing a dithiocarbamate group.…”
Section: Introductionmentioning
confidence: 98%
“…The dithiocarbamate group is an important functional group in synthetic organic chemistry and medicinal chemistry . It is a valuable pharmacophore that induces various biological activities when incorporated in a structure.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] The dithiocarbamate group is an important functional group in synthetic organic chemistry and medicinal chemistry. [15][16][17][18][19][20][21][22][23][24][25] It is a valuable pharmacophore that induces various biological activities when incorporated in a structure. Recently, various heterocyclic compounds containing dithiocarbamate groups including chromone-dithiocarbamate, [26] triazole-dithiocarbamates, [27] benzodioxole-dithiocarbamates, [28] benzimidazole-dithiocarbamates, [29] indoledithiocarbamates, [30] and quinazolinone-dithiocarbamate [31] have been introduced as efficient building blocks with anticancer and antibacterial activities (Scheme 1B).…”
Section: Introductionmentioning
confidence: 99%